Virtual Laboratory-Based Learning in Science Education to Improve Conceptual Understanding, Scientific Literacy, and Critical Thinking Skills - Utami, Ayu Rischi (Scientica Education Journal, 2025)
This study aims to examine the effectiveness of virtual laboratory-based learning in improving students’ conceptual understanding, scientific literacy, and critical thinking skills in science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of two groups: an experimental group taught using virtual laboratory-based learning integrated with inquiry-based activities and a control group taught using conventional methods. Data were collected through a conceptual understanding test, a scientific literacy test, and a critical thinking skills test. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). Furthermore, virtual laboratory-based learning significantly enhanced students’ ability to understand scientific concepts, interpret data, evaluate evidence, and solve problems. These findings suggest that virtual laboratories are an effective and innovative instructional strategy for promoting meaningful learning and developing essential competencies in science education.